Assessment of potential myopia risk factors, including chronotype, in Estonian adolescents: a cross-sectional study - Teele Palumaa; Delis Linntam; Reili Rebane; Kristel Harak; Mari Tamsalu; Katrin Sõnajalg; Karina Ülper; Svetlana Belova; Triin Keller; Marika Tammaru; Kadi Palumaa (BMC Ophthalmology)
Abstract Background Myopia is a growing healthcare concern worldwide. Increasing evidence suggests that sleep and circadian rhythms may be associated with myopia. Furthermore, the risk factors of myopia have not been studied in the Estonian population to date. This study aimed to evaluate chronotype, lifestyle factors, and parental myopia in relation to myopia in Estonian secondary school students. Methods Grade 10 students from three secondary schools in Tallinn, each with distinct focuses: one science-oriented, one arts-oriented, and one sports-oriented, were invited to participate. They underwent a comprehensive ocular examination, including cycloplegic autorefraction and ocular biometry. Chronotype was evaluated with the Morningness − Eveningness Questionnaire. Participants reported parental myopia and replied to a set of questions, separately for schooldays and free days, to indicate the amount of time they spent outdoors, doing near work and intermediate distance activities. Myopia was defined as cycloplegic SER ≤ − 0.50 D. Logistic regression analysis was performed to assess the association of the studied factors with myopia. Results A total of 123 students (57% female) participated in the study, with a mean age of 16.71 years (standard deviation 0.41). In a multivariable regression model, having two myopic parents was associated with higher odds of myopia (OR 3.78, 95% CI 1.15 − 12.42). We found no association between myopia and chronotype. Notably, time spent outdoors and doing near work or intermediate distance work did not affect the likelihood of having myopia. We observed that students attending the sports-oriented school had lower odds of myopia than those attending the science-oriented school (OR 0.12, 95% CI 0.03–0.51). Conclusion Chronotype was not associated with myopia in our study sample. Consistent with previous reports, we identified parental myopia as a myopia risk factor. Interestingly, there was no association between myopia and time spent outdoors or near work. However, the odds of myopia varied depending on the school attended by the participants, which may reflect the educational load or lifestyle of participants in earlier childhood.